2019
DOI: 10.1021/acscatal.9b00500
|View full text |Cite
|
Sign up to set email alerts
|

Silver-Catalyzed C- to N-Center Remote Arene Migration

Abstract: The first 1,4-arene migration from a carbon to a nitrogen center, induced by iminyl radicals generated from radical additions to vinyl azides, is reported. Two different modes of vinyl azide activation trigger this migration process, which offers a mild route for the synthesis of trifluoromethyl-or sulfonyl-substituted β-enamino ketones. Mechanistic studies reveal a dual role for the silver catalyst, and provide insight into the nature of the migration by demonstrating the positional influence of arene substit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 60 publications
2
20
0
Order By: Relevance
“…Various bases, including inorganic bases, such as K2CO3, 2,6-lutidine, and 4-dimethylaminopyridine, were examined. DBU was found as the optimal base (Table S1, † Entries 12,13,and 14). In summary, we found that an 88% isolated yield of the target product 3aa could be furnished at a constant current of 3.0 mA in MeOH with 10% TBAI as an electrolyte, DBU as a base, and graphite rod as an anode and cathode at room temperature (Table 1, Entry 8).…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Various bases, including inorganic bases, such as K2CO3, 2,6-lutidine, and 4-dimethylaminopyridine, were examined. DBU was found as the optimal base (Table S1, † Entries 12,13,and 14). In summary, we found that an 88% isolated yield of the target product 3aa could be furnished at a constant current of 3.0 mA in MeOH with 10% TBAI as an electrolyte, DBU as a base, and graphite rod as an anode and cathode at room temperature (Table 1, Entry 8).…”
mentioning
confidence: 77%
“…nucleophile acceptors [9] , electrophile acceptors [10] , 2H-azirine, vinylnitrene precursors [11] , enamine-type nucleophiles [12] , and 1,3-dipole [13] . Generally, α-substituted vinyl azides can be attacked by other radicals to generate imine radical [8,14] , which likely undergo hydrolysis and afford ketones [15] , or 1,3-H transfer and deliver enamines [16] or intramolecular cyclization and furnish N-heterocycles [17] .…”
mentioning
confidence: 99%
“…Ag catalyzed the multicomponent reaction of homopropargylic alcohols, trimethylsilyl azide and sodium sulfinates to access allyl sulfones in good to high yields ( Scheme 227 ). 336 The symmetrical homopropargylic alcohol migration products are consistent, whereas the non-symmetric homopro-pargylic alcohols showed interesting chemoselectivity of the migration of the arene groups. The electronic properties of the arylsulfinates revealed a relatively low influence, and alkyl sulfinates also showed comparable efficiency.…”
Section: Applications Of Sodium Sulfinatesmentioning
confidence: 95%
“…In 2019, the 1,4-arene migration from carbon to nitrogen center which was induced by iminyl radicals was reported by Bi group. [43] This reaction provide an efficient protocol for the synthesis of sulfonyl-substituted β-enamino ketones. Radical mechanism was suggested for this transformation.…”
Section: Sulfonylation/noncyclization With Alkynesmentioning
confidence: 99%